Iron oxide / graphene composite electrode material and preparation method thereof
By combining iron oxide with graphene and adjusting the ratio, combined with annealing treatment, iron oxide/graphene composite electrode material was prepared, which solved the problems of low power density and poor circulation performance of lithium-ion batteries, and achieved battery performance with high energy density, high power density and long cycle life.
Patent Information
- Application Number
- CN202411800322.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-11
AI Technical Summary
Existing lithium-ion batteries have problems with low power density and poor cycle performance. Supercapacitors also have shortcomings in energy density, which is difficult to meet the needs of high energy density, high power density and long cycle life of electric vehicles, electronic storage devices, and power grid energy storage devices.
By compounding iron oxide with graphene, adjusting the ratio of graphene to metal oxide, optimizing electrochemical properties, and improving the crystallinity of iron oxide particles through annealing treatment, enhancing conductivity and mechanical stability, iron oxide/graphene composite electrode material was prepared.
The reduction of charge transfer impedance and the improvement of electrochemical performance are achieved, and the circulation performance of the battery is significantly improved, solving the problem of poor cycle stability rate performance caused by volume changes and particle powdering.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite electrode preparation, and specifically relates to an iron oxide / graphene composite electrode material and a preparation method thereof. Background Art
[0002] With the rapid development of the global economy and the reduction of fossil energy, humans are urging themselves to focus on developing renewable green energy. The demand for new energy is increasing day by day, and the direction headed by electric energy has become a research hotspot. Among them, supercapacitors and lithium-ion batteries are currently the most promising electrochemical energy storage tools, and are favored by the industry for their high energy density, high stable working voltage and no memory effect.
[0003] However, existing lithium-ion batteries generally have problems with low power density and poor cycle performance. In contrast, supercapacitors have great advantages in power density and cycle life, but are still limited by low energy density. However, practical electrical equipment such as electric vehicles, electronic storage devices and grid energy storage are eager to have energy storage devices that have the excellent performance of high energy density, high power density and long cycle life.
[0004] Among battery electrode materials, transition metal oxides have been widely studied due to their high specific capacity. Among them, iron oxide has attracted research interest due to its high specific capacity (1007mAh / g), low cost, abundant resources, and no pollution. However, the excessive volume deformation of iron oxide materials during the charge and discharge cycle leads to degradation of the electrode structure and poor cycle performance, which seriously restricts its application in lithium-ion batteries. Through the composite of iron oxide and graphene, on the one hand, the electrical conductivity of the electrode material is improved, and on the other hand, the large specific surface area of graphene provides a buffer space for the volume deformation of iron oxide, which can greatly improve the electrochemical performance of the electrode.
[0005] Therefore, how to use iron oxide and graphene to obtain a new electrode material to improve the conductivity of the battery while also improving the cycle performance of the battery has become a problem that needs to be solved. Summary of the invention
[0006] The first purpose of the present invention is to propose a method for preparing an iron oxide / graphene composite electrode material, which has the advantages of easy availability of raw materials, independence of equipment, and simple process; by adjusting the ratio of graphene to metal oxide, the electrochemical performance of the product can be optimized.
[0007] The second object of the present invention is to provide an iron oxide / graphene composite electrode material that has good electrical conductivity and can significantly improve the cycle performance of the battery.
[0008] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing an iron oxide / graphene composite electrode material comprises the following steps: using scrap iron as a raw material, reacting it with an acid solution at a controlled temperature after pretreatment, and cooling and crystallizing it to obtain Fe(NO3)3·9H2O; mixing Fe(NO3)3·9H2O with HCl to obtain a mixed solution, adding ultrasonically dispersed graphene oxide dispersion, adjusting the pH, performing a hydrothermal reaction, and obtaining a sample by solid-liquid separation; and obtaining the iron oxide / graphene composite electrode material through annealing.
[0010] Furthermore, the pretreatment step is: adding the scrap iron sheets or iron filings into the soda ash solution for soaking, stirring and heating to 60-85°C, naturally cooling to room temperature, filtering to remove the liquid phase, retaining the solids and naturally air-drying to obtain treated fine iron filings.
[0011] Furthermore, the volume ratio of the mixed liquid to the dispersed liquid is 5-11:7-13.
[0012] Further, Fe(NO3)3·9H2O is mixed with HCl to prepare Fe-containing 3+ 0.3mol / L, Cl - 0.5mol / L mixed solution.
[0013] Furthermore, the ultrasonic power is 300 W, and the time is 30 to 45 minutes.
[0014] Further, the pH was adjusted to 1.5 by HCl / hydrogen peroxide.
[0015] Furthermore, the temperature of the hydrothermal reaction is 115-135° C., and the reaction time is 7-8 h.
[0016] Furthermore, the annealing treatment is carried out in an argon atmosphere, the annealing temperature is 350-360° C., and the time is 2-3 hours.
[0017] Furthermore, the preparation method of any of the above-mentioned iron oxide / graphene composite electrode materials comprises the following steps:
[0018] (1) adding scrap iron or iron filings to a soda ash solution, soaking, stirring and heating to 60-85° C., cooling naturally to room temperature, filtering to remove the liquid phase, retaining the solids and naturally air-drying to obtain treated fine iron filings;
[0019] (2) 10 L of 62% nitric acid was mixed with 3 L of water to obtain an acid solution, the temperature was controlled at 42-50° C., 5 kg of fine iron filings obtained in step (1) were slowly transferred to the acid solution, heated to 68° C., stirred for reaction for 2-3 h, filtered, the filtrate was allowed to stand, seed crystals were added, and naturally cooled and crystallized to obtain Fe(NO3)3·9H2O crystals, the Fe(NO3)3·9H2O crystals were washed with 20% nitric acid solution to remove impurities on the crystal surface, and finally Fe(NO3)3·9H2O was obtained;
[0020] (3) Dissolve Fe(NO3)3·9H2O in HCl aqueous solution to prepare Fe 3+ 0.3mol / L, Cl - The invention discloses a method for preparing an iron oxide / graphene composite electrode material, wherein the method comprises the steps of: preparing a 0.5 mol / L mixed solution; adding graphene oxide to deionized water, and performing ultrasonic dispersion at 300 W for 30 to 45 min; mixing the dispersion and the mixed solution in a volume ratio of 5 to 11:7 to 13, and adding HCl / hydrogen peroxide to adjust the pH to 1.5, and continuously stirring for 15 to 30 min. After the system is stable, the mixture is transferred to a reactor, reacted at 115 to 135° C. for 7 to 8 h, and centrifuged after natural cooling to obtain a solid, and rinsing the solid with deionized water and ethanol for 3 to 5 times in sequence. After vacuum drying, the sample is annealed in an argon atmosphere at 350 to 360° C. for 2 to 3 h to obtain an iron oxide / graphene composite electrode material.
[0021] Furthermore, the iron oxide / graphene composite electrode material is prepared by any of the above methods.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1) The material prepared by the present invention has a small charge transfer impedance and good electrochemical performance. The electrochemical performance of the material can be optimized by adjusting the ratio of graphene to metal oxide.
[0024] 2) The present invention improves the crystallinity of iron oxide particles through annealing treatment, further improves their conductivity and mechanical stability, and can effectively solve the problem of poor cycle stability and rate performance caused by excessive volume change and particle pulverization during multiple charge and discharge cycles.
[0025] 3) The electrode composite material prepared by the present invention has the highest specific capacity and the smallest cycle loss. DETAILED DESCRIPTION
[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.
[0027] Unless otherwise specified, the raw materials used in the following examples are commercially available products.
[0028] Example 1
[0029] A method for preparing an iron oxide / graphene composite electrode material, comprising the following steps:
[0030] (1) adding scrap iron or iron filings to a soda ash solution, soaking, stirring and heating to 60-85° C., cooling naturally to room temperature, filtering to remove the liquid phase, retaining the solids and naturally air-drying to obtain treated fine iron filings;
[0031] (2) 10 L of 62% nitric acid was mixed with 3 L of water to obtain an acid solution, the temperature was controlled at 42-50° C., 5 kg of fine iron filings obtained in step (1) were slowly transferred to the acid solution, heated to 68° C., stirred for reaction for 2-3 h, filtered, the filtrate was allowed to stand, seed crystals were added, and naturally cooled and crystallized to obtain Fe(NO3)3·9H2O crystals, the Fe(NO3)3·9H2O crystals were washed with 20% nitric acid solution to remove impurities on the crystal surface, and finally Fe(NO3)3·9H2O was obtained;
[0032] (3) Dissolve Fe(NO3)3·9H2O in HCl aqueous solution to prepare Fe 3+ 0.3mol / L, Cl - 0.5 mol / L mixed solution; adding graphene oxide to deionized water, 300W ultrasonic dispersion for 45 minutes; mixing the dispersion and the mixed solution in a volume ratio of 5:13, and adding HCl / hydrogen peroxide to adjust the pH to 1.5, stirring for 15 minutes, after the system is stable, transferring it to a reactor, reacting at 135°C for 7 hours, cooling naturally and centrifuging to obtain a solid, rinsing it with deionized water and ethanol for 3 to 5 times in sequence, and after vacuum drying, annealing the sample in an argon atmosphere at 350°C for 2 hours to obtain an iron oxide / graphene composite electrode material.
[0033] Example 2
[0034] A method for preparing an iron oxide / graphene composite electrode material, comprising the following steps:
[0035] (1) adding scrap iron or iron filings to a soda ash solution, soaking, stirring and heating to 60-85° C., cooling naturally to room temperature, filtering to remove the liquid phase, retaining the solids and naturally air-drying to obtain treated fine iron filings;
[0036] (2) 10 L of 62% nitric acid was mixed with 3 L of water to obtain an acid solution, the temperature was controlled at 42-50° C., 5 kg of fine iron filings obtained in step (1) were slowly transferred to the acid solution, heated to 68° C., stirred for reaction for 2-3 h, filtered, the filtrate was allowed to stand, seed crystals were added, and naturally cooled and crystallized to obtain Fe(NO3)3·9H2O crystals, the Fe(NO3)3·9H2O crystals were washed with 20% nitric acid solution to remove impurities on the crystal surface, and finally Fe(NO3)3·9H2O was obtained;
[0037] (3) Dissolve Fe(NO3)3·9H2O in HCl aqueous solution to prepare Fe 3+ 0.3mol / L, Cl - 0.5 mol / L mixed solution; adding graphene oxide to deionized water, 300W ultrasonic dispersion for 45 minutes, to obtain a dispersion; mixing the dispersion and the mixed solution in a volume ratio of 7:9, and adding HCl / hydrogen peroxide to adjust the pH to 1.5, stirring for 15 minutes, after the system is stable, transferring it to a reactor, reacting at 115°C for 8 hours, naturally cooling and centrifuging to obtain a solid, rinsing it with deionized water and ethanol for 3 to 5 times in sequence, and after vacuum drying, annealing the sample in an argon atmosphere at 360°C for 3 hours to obtain an iron oxide / graphene composite electrode material.
[0038] Example 3
[0039] A method for preparing an iron oxide / graphene composite electrode material, comprising the following steps:
[0040] (1) adding scrap iron or iron filings to a soda ash solution, soaking, stirring and heating to 60-85° C., cooling naturally to room temperature, filtering to remove the liquid phase, retaining the solids and naturally air-drying to obtain treated fine iron filings;
[0041] (2) 10 L of 62% nitric acid was mixed with 3 L of water to obtain an acid solution, the temperature was controlled at 42-50° C., 5 kg of fine iron filings obtained in step (1) were slowly transferred to the acid solution, heated to 68° C., stirred for reaction for 2-3 h, filtered, the filtrate was allowed to stand, seed crystals were added, and naturally cooled and crystallized to obtain Fe(NO3)3·9H2O crystals, the Fe(NO3)3·9H2O crystals were washed with 20% nitric acid solution to remove impurities on the crystal surface, and finally Fe(NO3)3·9H2O was obtained;
[0042] (3) Dissolve Fe(NO3)3·9H2O in HCl aqueous solution to prepare Fe 3+ 0.3mol / L, Cl -0.5 mol / L mixed solution; adding graphene oxide to deionized water, 300W ultrasonic dispersion for 30 minutes; mixing the dispersion and the mixed solution in a volume ratio of 11:10, and adding HCl / hydrogen peroxide to adjust the pH to 1.5, stirring for 30 minutes, after the system is stable, transferring it to a reactor, reacting at 125°C for 7 hours, naturally cooling and centrifuging, and rinsing the solid with deionized water and ethanol for 3 to 5 times in sequence. After vacuum drying, annealing the sample in an argon atmosphere at 355°C for 3 hours to obtain an iron oxide / graphene composite electrode material.
[0043] Example 4
[0044] A method for preparing an iron oxide / graphene composite electrode material, comprising the following steps:
[0045] (1) adding scrap iron or iron filings to a soda ash solution, soaking, stirring and heating to 60-85° C., cooling naturally to room temperature, filtering to remove the liquid phase, retaining the solids and naturally air-drying to obtain treated fine iron filings;
[0046] (2) 10 L of 62% nitric acid was mixed with 3 L of water to obtain an acid solution, the temperature was controlled at 42-50° C., 5 kg of fine iron filings obtained in step (1) were slowly transferred to the acid solution, heated to 68° C., stirred for reaction for 2-3 h, filtered, the filtrate was allowed to stand, seed crystals were added, and naturally cooled and crystallized to obtain Fe(NO3)3·9H2O crystals, the Fe(NO3)3·9H2O crystals were washed with 20% nitric acid solution to remove impurities on the crystal surface, and finally Fe(NO3)3·9H2O was obtained;
[0047] (3) Dissolve Fe(NO3)3·9H2O in HCl aqueous solution to prepare Fe 3+ 0.3mol / L, Cl - 0.5 mol / L mixed solution; adding graphene oxide to deionized water, 300W ultrasonic dispersion for 45 minutes, to obtain a dispersion; mixing the dispersion and the mixed solution in a volume ratio of 11:8, and adding HCl / hydrogen peroxide to adjust the pH to 1.5, stirring for 30 minutes, after the system is stable, transferring it to a reactor, reacting at 135°C for 8 hours, naturally cooling and centrifuging to obtain a solid, rinsing it with deionized water and ethanol for 3 to 5 times in sequence, and after vacuum drying, annealing the sample in an argon atmosphere at 360°C for 3 hours to obtain an iron oxide / graphene composite electrode material.
[0048] Example 5
[0049] A method for preparing an iron oxide / graphene composite electrode material, comprising the following steps:
[0050] (1) adding scrap iron or iron filings to a soda ash solution, soaking, stirring and heating to 60-85° C., cooling naturally to room temperature, filtering to remove the liquid phase, retaining the solids and naturally air-drying to obtain treated fine iron filings;
[0051] (2) 10 L of 62% nitric acid was mixed with 3 L of water to obtain an acid solution, the temperature was controlled at 42-50° C., 5 kg of fine iron filings obtained in step (1) were slowly transferred to the acid solution, heated to 68° C., stirred for reaction for 2-3 h, filtered, the filtrate was allowed to stand, seed crystals were added, and naturally cooled and crystallized to obtain Fe(NO3)3·9H2O crystals, the Fe(NO3)3·9H2O crystals were washed with 20% nitric acid solution to remove impurities on the crystal surface, and finally Fe(NO3)3·9H2O was obtained;
[0052] (3) Dissolve Fe(NO3)3·9H2O in HCl aqueous solution to prepare Fe 3+ 0.3mol / L, Cl - 0.5 mol / L mixed solution; adding graphene oxide to deionized water, 300W ultrasonic dispersion for 45 minutes, to obtain a dispersion; mixing the dispersion and the mixed solution in a volume ratio of 9:10, and adding HCl / hydrogen peroxide to adjust the pH to 1.5, stirring for 15 to 30 minutes, after the system is stable, transferring it to a reactor, reacting at 135°C for 8 hours, naturally cooling and centrifuging to obtain a solid, rinsing it with deionized water and ethanol for 3 to 5 times in sequence, and after vacuum drying, annealing the sample in an argon atmosphere at 360°C for 3 hours to obtain an iron oxide / graphene composite electrode material.
[0053] Comparative Example 1
[0054] Preparation method of iron oxide / graphene composite electrode material:
[0055] 90 mg of graphene oxide was ultrasonically dispersed in 120 mL of a mixed solvent (the volume ratio of water to ethanol was 5:1) deionized water, the ultrasonic power and time were 300 W and 1 h respectively, to obtain a uniformly mixed graphene oxide dispersion, 1.296 g of ferric chloride hexahydrate was added, and after magnetic stirring for 60 min to mix evenly, it was placed in an electric heated blast drying oven for solvent thermal treatment at 160 ° C for 20 h, and filtered, washed, and freeze-dried to obtain a graphene / iron oxide composite material.
[0056] Comparative Example 2
[0057] Different from Example 3, no annealing process is performed.
[0058] Comparative Example 3
[0059] Different from Example 3, no mixed solution was prepared, and Fe(NO3)3·9H2O was directly added to the dispersion.
[0060] The electrochemical performance tests (at a current density of 100 mA / g) were performed on the negative electrode materials obtained in the above Examples 1 to 5 and Comparative Examples 1 to 3, and the results are shown in Table 1 below.
[0061] Table 1 Comparison of electrochemical performance of Examples 1 to 5 and Comparative Examples 1 to 3
[0062] 50 cycles specific capacity mAh / g 100 cycles specific capacity mAh / g Example 1 589 473 Example 2 612 522 Example 3 645 561 Example 4 609 483 Example 5 587 436 Comparative Example 1 496 371 Comparative Example 2 564 489 Comparative Example 3 533 433
[0063] It can be seen from Table 1 that in Examples 1 to 5 of the present invention, when the dispersion and the mixed solution are mixed at a volume ratio of 11:10, the prepared electrode composite material has the highest specific capacity and the smallest cycle loss; it can be seen from Example 3 and Comparative Example 2 that the present invention improves the crystallinity of iron oxide particles through annealing treatment, further improves its conductivity and mechanical stability, and can effectively solve the problem of poor cycle stability and rate performance caused by excessive volume change and particle pulverization during multiple charge and discharge cycles. 3+ The mixed solution has more abundant active sites for electrolyte contact and reaction. At the same time, the iron oxide shuttle particles also act as spacers to prevent the spontaneous restacking of graphene sheets, increase the interlayer spacing, and facilitate rapid electron and ion transport between graphene sheets.
[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an iron oxide / graphene composite electrode material, characterized in that: Scrap iron is used as raw material, and after pretreatment, it is reacted with an acid solution under controlled temperature, and cooled and crystallized to obtain Fe(NO3)3·9H2O; Fe(NO3)3·9H2O is mixed with HCl to obtain a mixed solution, and then an ultrasonically dispersed graphene oxide dispersion is added, and after adjusting the pH, a hydrothermal reaction is carried out, and a solid-liquid separation is performed to obtain a sample, which is annealed to obtain an iron oxide / graphene composite electrode material.
2. The method for preparing the iron oxide / graphene composite electrode material according to claim 1, characterized in that: The pretreatment step is: adding the scrap iron sheets or iron filings into a soda ash solution for soaking, stirring and heating to 60-85° C., naturally cooling to room temperature, filtering to remove the liquid phase, retaining the solids and naturally air-drying to obtain treated fine iron filings.
3. The method for preparing the iron oxide / graphene composite electrode material according to claim 1, characterized in that: The volume ratio of the mixed liquid to the dispersed liquid is 5-11:7-13.
4. The method for preparing the iron oxide / graphene composite electrode material according to claim 1, characterized in that: Fe(NO3)3·9H2O was mixed with HCl to prepare Fe-containing 3+ 0.3mol / L, Cl - 0.5mol / L mixed solution.
5. The method for preparing the iron oxide / graphene composite electrode material according to claim 1, characterized in that: The ultrasonic power is 300W and the time is 30 to 45 minutes.
6. The method for preparing the iron oxide / graphene composite electrode material according to claim 1, characterized in that: The pH was adjusted to 1.5 with HCl / hydrogen peroxide.
7. The method for preparing the iron oxide / graphene composite electrode material according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 115-135°C, and the reaction time is 7-8h.
8. The method for preparing the iron oxide / graphene composite electrode material according to claim 1, characterized in that: The annealing treatment is carried out in an argon atmosphere at a temperature of 350 to 360° C. for 2 to 3 hours.
9. The method for preparing the iron oxide / graphene composite electrode material according to any one of claims 1 to 8, characterized in that: Here are the steps: (1) adding scrap iron or iron filings to a soda ash solution, soaking, stirring and heating to 60-85° C., cooling naturally to room temperature, filtering to remove the liquid phase, retaining the solids and naturally air-drying to obtain treated fine iron filings; (2) 10 L of 62% nitric acid and 3 L of water are mixed evenly to obtain an acid solution, the temperature is controlled at 42-50° C., 5 kg of fine iron filings obtained in step (1) are slowly transferred to the acid solution, heated to 68° C., stirred for reaction for 2-3 h, filtered, the filtrate is allowed to stand, seed crystals are added, and naturally cooled and crystallized to obtain Fe(NO3)3·9H2O crystals, the Fe(NO3)3·9H2O crystals are washed with 20% nitric acid solution to remove impurities on the crystal surface, and finally Fe(NO3)3·9H2O is obtained; (3) Dissolve Fe(NO3)3·9H2O in HCl aqueous solution to prepare Fe 3+ 0.3mol / L, Cl - 0.5 mol / L mixed solution; adding graphene oxide to deionized water, and ultrasonically dispersing for 30 to 45 minutes at 300W; mixing the dispersion and the mixed solution in a volume ratio of 5 to 11:7 to 13, and adding HCl / hydrogen peroxide to adjust the pH to 1.5, stirring for 15 to 30 minutes, transferring the system to a reactor after it stabilizes, reacting at 115 to 135° C. for 7 to 8 hours, cooling naturally and centrifuging to obtain a solid, rinsing it with deionized water and ethanol for 3 to 5 times in sequence, and after vacuum drying, annealing the sample in an argon atmosphere at 350 to 360° C. for 2 to 3 hours to obtain an iron oxide / graphene composite electrode material.
10. The iron oxide / graphene composite electrode material prepared according to any one of claims 1 to 9.